Five new leafhopper species of the genus Typhlocyba Germar (Hemiptera: Cicadellidae: Typhlocybinae) from China - Huang, Min; Zhang, Ya-Lin (Zootaxa, 2009)
Five species, T. napoensis, T. bilaminata, T. serrata, T. triannulata and T. tubercula spp. nov., of genus Typhlocyba Germar from China are described and illustrated. A key to males of Chinese Typhlocyba species is provided.